Implementing School-Wide Positive Behavioural Interventions and Supports to Better Meet the Needs of Indigenous Students. (September 2014) - McIntosh, Kent; Moniz, Christina; Craft, Calli B.; Golby, Risha; Steinwand-Deschambeault, Tammy
This article examines the need for and importance of culturally responsive behaviour support for Indigenous students. Many of the educational challenges currently faced by Indigenous students can be explained by cultural disconnect and a mismatch between school expectations and cultural values. Principles of Indigenous approaches to behaviour support are described and compared with school-wide positive behavioural interventions and supports (PBIS), a framework for building a positive school culture that shows promise in relation to culturally responsive practice. The authors provide a brief overview of PBIS and adaptations of this practice to meet the needs of Indigenous students. A descriptive case study of PBIS implementation in a high school in the Northwest Territories provides an example of culturally responsive implementation of PBIS.